Analisis Kesiapsiagaan Siswa dalam Menghadapi Bencana Kekeringan melalui Media Booklet - Fajar Wulandari (Tarbawi : Jurnal Ilmu Pendidikan, 2019)
Abstract. This study aims to study high school students who discuss the problem of drought in Singkawang City, with the help of learning media preparedness booklets. Booklet learning media is an alternative for students in SMA 1 to support geography learning about education, by understanding learning outcomes and student responses to the application of learning media booklets for natural disaster mitigation and adaptation materials. This study uses research and development research methods, the steps taken on 4 resistance are (1) defining (2) design (3) developing (4) disseminate is defining, designing, developing, and distributing. Research place in Singkawang City High School in the even semester of the 2017-2018 academic year. The study design used purposive random sampling. The subject of this study was a class XI high school student in Singkawang City, in Singkawang 1 Public High School. Quantitative data analysis using experimental methods and percentage techniques, data collection using preparedness and documentation questionnaires. The data analysis technique used was anava and anava further test. The prerequisite test used is the normality test and homogeneity test. The results showed the validation by high school geography teachers reached a percentage of 84% and expert media validation was 77%. The booklet that can be used without revision. Hypothesis testing results that prove the probability value> 0.05 then Ho is accepted and probability value <0.05, then Ho is rejected and if the value of sig (2-tailed) 0,000 <0.05 then Ho is rejected which means supporting Booklet learning media affect the preparedness of students at SMAN Kota Singkawang. The results of student preparedness in the face of disasters indicate that there are students who are less prepared and almost 33.33% who are not ready to face natural difficulties. However, after being given learning with the help of a media booklet, 99.98% of students who understood in the act of suffering from drought natural disasters were obtained. The conclusion in this study is a media learning book that is suitable for use in the teaching and learning process in the classroom. Media Learning Books that are effective in improving and improving student learning outcomes in facing natural challenges in Singkawang City. Abstrak. Penelitian ini bertujuan untuk mengetahui kesiapsiagaan siswa SMA dalam menghadapi bencana kekeringan di Kota Singkawang, dengan berbantu media pembelajaran booklet kesiapsiagaan. Media pembelajaran booklet merupakan alternatif bagi siswa di SMA Negeri 1 untuk penunjang pembelajaran geografi khusunya pada pendidikan kebencanaan, dengan mengetahui perbedaan hasil belajar dan respon siswa terhadap penerapan media pembelajaran booklet materi mitigasi dan adaptasi bencana alam. Penelitian ini menggunakan metode penelitian research and development, langkah-langkah yang dilakukan meliputi 4 tahan yaitu (1) define (2) design (3) develop (4) dessemiate merupakan pendefinisian, perancangan, pengembangan, dan penyebaran. Tempat penelitian di SMA Negeri Kota Singkawang pada semester genap tahun ajaran 2017-2018. Rancangan penelitian menggunakan purposive random Sampling. Subjek penelitian ini adalah siswa kelas XI SMA di Kota Singkawang, di SMA Negeri 1 Kota Singkawang. Analisis data secara kuantitatif dengan metode eksperimen dan teknik persentase, pengumpulan data dengan menggunakan angket kesiapsiagaan dan dokumentasi. Teknik analisis data yang digunakan adalah anava dan uji lanjut anava. Uji prasyarat yang digunakan yaitu uji normalitas dan uji homogenitas. Hasil penelitian menunjukkan bahwa validasi oleh guru geografi SMA mencapai persentase sebesar 84% dan validasi ke media ahli sebesar 77%. Secara keseluruhan hasil menunjukkan bahwa perangkat pembelajaran dan media booklet dapat digunakan tanpa revisi. Hasil uji hipotesis menunjukkan perbandingan nilai probabilitas > 0,05 maka Ho diterima dan nilai probabilitas < 0,05 maka Ho ditolak dan jika nilai sig(2-tailed) 0,000 < 0,05 maka Ho ditolak yang berarti pemberian media pembelajaran Booklet dalam penelitian telah mempengaruhi kesiapsiagaan siswa SMAN Kota Singkawang. Hasil kesiapsiagaan siswa dalam menghadapi bencana menunjukkan terdapat siswa yang kurang siap dan hampir siap sebesar 33,33% yang kurang siap dalam menghadapi bencana alam kekeringan. Namun setelah diberikan pembelajaran dengan bantuan media booklet didapatkan 99,98% siswa yang telah paham dalam bertindak mengahdapi bencana alam kekeringan. Kesimpulan dalam penelitian ini adalah media pembelajaran booklet layak digunakan dalam proses belajar mengajar di kelas. Media pembelajaran Booklet efektif dalam mempengaruhi dan meningkatkan hasil kesiapsiagaan siswa dalam menghadapi bencana alam di Kota Singkawang.